Sosialisasi Pemanfaatan Software Open Source di SMK Muhammadiyah 1 Surakarta - Husni Thamrin; Dedi Ary Prasetya; Ady Purna Kurniawan (WARTA LPM, 2010)
Embrace of open source software (OSS) has not been widespread although users ofOSS will gain a lot of benefits and the society and the nation will get many advantages.This writing describes an observation to the understanding and attitude of a group ofstudents towards the use of OSS. The students come from SMK Muhammadiyah 1Surakarta which is a vocational school in Surakarta owned by Muhammadiyahorganization. A survey was conducted during an OSS campaign. Students were facedwith two sets of questionnaires; the first set was given prior and the seoncd after thecampaign. The first set was aimed at identifying the computer literacy of the studentsand their understanding of the open source concept. The second set was aimed atexploring their understanding and attitude towards the use of OSS. Observation showedthat the campaign activity improved students understanding of open source conceptand enhance their attitude to use OSS. However, students were to some extent pragmatic when they were opted to select which software to use to accomplish a task.